Interrelationships of deformity, impairment, disability and handicap in adolescent idiopathic thoracic scoliosis - Kearon, Michael Clive (My University, 1992)
The purpose of this thesis was to quantify spinal deformity (nature and extent), pulmonary impairment (mechanical and gas exchanging properties), disability (working capacity) and handicap (exertional symptoms) in a large group of subjects with idiopathic scoliosis, so that the relationships between these elements could be determined. It was anticipated that these relationships would be more variable (weaker) than is commonly implied. A further aim therefore, was to identify additional factors which contribute to pulmonary impairment, disability and exertional symptoms in these subjects. The influences of respiratory muscle, peripheral muscle and cardiac factors on these relationships were considered to be potentially important.
Seventy-nine subjects (M:F 13:66; age 21 (SD 10.1)) with mild-moderate idiopathic thoracic scoliosis (Cobb angle 45° (SD 18.4)) were studied.
Pulmonary impairment in the group as a whole was moderate, with the vital capacity being reduced to 79% of predicted (SD 13.6). Angle of scoliosis was one of four features of the spinal deformity which contributed to pulmonary impairment; longer curves (number of vertebrae), higher curve position and loss of the normal thoracic kyphosis also had an additive influence.
Disability was significant, with exercise capacity being reduced to 86% (SD 17.4) of predicted; nature and extent of spinal deformity was unrelated to disability. Similarly, there was no direct relationship between pulmonary impairment and the extent of disability.
Application of psychophysical symptom rating scale showed that both the intensity of breathlessness and leg effort were increased during exercise, but most subjects stopped exercising due to leg effort rather than breathlessness. This finding focused attention on the relationship of disability to peripheral muscle factors.
Leg muscle volume and lean body mass were closely related to maximum working capacity. The relationship of leg muscle volume to maximum oxygen consumption was similar to that previously reported in normal subjects; this suggests that reduced muscle bulk, rather than qualitative muscular differences, is a particularly important contributor to disability. Once between subject differences in muscularity were taken into account, an additional influence of pulmonary impairment on disability was evident.
A higher heart rate response during exercise was also found in more disabled subjects, suggesting that cardiac performance may also influence work capacity in this group. (Abstract shortened by UMI.)
Keywords: Pharmacology; Physiology; Pharmacology